Powersolarz Sdn. Bhd. / Muhammad Asyraf Haikal Mohd Hisarudin - Mohd Hisarudin, Muhammad Asyraf Haikal (2020)
Powersolarz Sdn. Bhd. is the company establish and grow in the segment of hardware consuming technologies. The company is a start-up company that will offer and provide a solar power bank name Solarz for customers. Solarz serves the customers with stylish and latest designs, styles, colours of the solar power bank to cater customer needs. Besides, the power bank also designed with high-quality materials to achieve high satisfaction of customers. Other than that, it is also small in size to facilitate consumers to bring everywhere. The management of the business consists of the General Manager name Asyraf Haikal. He assisted by 5 lead workers whereas Abu Bin Abi as Marketing Manager, Salleh Bin Mohd as Finance Manager, Adam Bin Ahmad as Electrical Engineering Manager, Halim Bin Saari as Operation Manager, Kamal Bin Mat as Human Resource Manager. They are highly skilled and talented in their respective fields for having working experience with various companies before. They will ensure that they will be performed in doing tasks together although they different duties and portfolios in order to serve in Powersolarz Sdn Bhd.